The confluence of radiotherapy and immunotherapy - Weichselbaum, Ralph R.; Fu, Yang-Xin; Burnette, Byron C. (Frontiers in Oncology, 2012)
Radiotherapy has been considered a local modality and outcomes have emphasized local and regional control of tumors. Recent data suggests that radiotherapy may activate the immune system and the combination of radiation therapy and immune therapies may have the potential to improve both local and distant control of tumor deposits. Below we review principals underlying the concepts of combining both modalities.